Long-term impact of biofertilization on soil health and nutritional quality of organic basmati rice in a typic ustchrept soil of India - Kumawat, Anita; Kumar, Dinesh; Shivay, Y. S.; Bhatia, Arti; Rashmi, I.; Yadav, Devideen; Kumar, Ashok (Frontiers in Environmental Science, 2023)
Healthy soils are the foundation for producing healthy food and creating a healthy environment. Therefore, we assessed the changes in soil physical and chemical properties, and their impact on yield, quality, and nutritional status of rice grains in a long-term organic basmati rice-based cropping system in a typic Ustchrept Soil of India. The experiment was laid out in a strip plot design with three replications. The vertical strips consisted of two rice-based cropping systems i.e., basmati rice-wheat-mung bean (RWM) and basmati rice-wheat-sesbania (RWS), whereas, seven combinations of different organic materials and biofertilizers (BF) were assigned to horizontal strips viz., control (no manure application), farmyard manure (FYM), vermicompost (VC), FYM + crop residues (CR), VC+CR, FYM+CR+BF, and VC+CR+BF. The results revealed that soil moisture content (SMC), soil organic carbon (SOC), soil total N, and soil available P, Fe, Zn, Mn, and Cu were significantly higher under the RWS system than in RWM. The application of organic manures either alone or in conjunction with CR and BF significantly lowered the soil pH (~3.0%), EC (43.1-45.8%), and BD (3.3-9.2%) as compared to the control. Water holding capacity (WHC), SMC and SOC were increased by 5.7-14.7%, 8.7-49.3%, and 35.3-76.5%, respectively under single or co-application of FYM/VC with CRs and BFs as compared to control. Similarly, sole or conjoint application of organic manures, CR, and BF significantly enhanced the soil available macro (N, P, and K) and micro (Fe, Zn, Mn, and Cu) nutrients over the control. Grain yield, protein content, N uptake, and cooking quality parameters were significantly higher under the RWS system than RWM. However, the Zn concentration and its uptake by grains were significantly higher under the RWM system over RWS. The grain yield was significantly increased by 25.8-49.2% under different organic nutrient management options over control. The concentration of N, P, K, Fe, Zn, Mn, and Cu was significantly improved by 9.7-11.3%, 45.5-63.6%, 16.7-20.8%, 66.9-74.1%, 72.9-81.9%, 87.1-97.0%, and 48.9-67.2%, respectively under co-application of FYM/VC with CR and BF compared to control. Thus, our results indicate that improved soil properties could significantly increase the physical and nutritional quality of basmati rice grain.